Preserving Oral Tradition amid the COVID-19 Pandemic: A Cultural Adaptation in Salawat Dulang - Eka Meigalia; Yerri Satria Putra; Muhammad Jauhari Sofi (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2021)
The COVID-19 pandemic has affected various aspects of people's lives, including oral traditions. In Minangkabau, oral traditions are in danger of being lost or forgotten by the community due to the pandemic. During the pandemic, oral tradition performances involve only few people, though the performances typically require the presence of many people. This current study aims to explain various things that happened to the oral tradition in Minangkabau amid the COVID-19 pandemic, especially Salawat Dulang. It uses a qualitative approach with data collection techniques through observation, note-taking, and interviews. The study found that the Minangkabau oral tradition, especially Salawat Dulang, survived and continued amid the pandemic because it implements various forms of changes and adjustments. These changes and adjustments include the involvement of virtual and direct media. There are very few audiences attending the live performances, and they must strictly adhere to health protocols. Performers also use social media as a means to maintain the existence of their traditions. In this sense, they see the conditions related to the COVID-19 pandemic as a source of inspiration to create the spoken texts. These findings imply the important role of all the performers, the community, and the government in proposing efforts to preserve this oral tradition.